Pengembangan E-Modul Berbasis Pendekatan RME Menggunakan Kue Tradisional Bengkulu untuk Meningkatkan Kemampuan Pemecahan Masalah pada Materi Bangunan Datar Kelas IV SD - Endang Putriani; Agus Susanta; Irwan Koto (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
The purpose of this study is to determine the feasibility of material, language, design, student response, and product effectiveness resulting from the development of e-modules based on the RME approach using traditional Bengkulu cakes to improve problem solving skills in flat shape material for class IV SD. This research is a Research and Development (R&D) study. The model used in the development is the 4-D model. The subjects in the study were students of SDN 53 Kaur, which consisted of 12 students in class IV A as the control class, and 13 students in class IV B as the experimental class. The instruments used in this study were interview guideline, questionnaires, and problem-solving test questions in the form of essay for pretest and posttest. The data analysis technique used Aiken's V, Interrater Reliability, normality test, homogeneity test, t-test and N-gain score. From the research results it is known that the results of material, language, and design validation, as well as student responses to the use of e-modules are very feasible and well used in learning so that students are motivated to learn.